2021
DOI: 10.3390/app11030904
|View full text |Cite
|
Sign up to set email alerts
|

The Use of the Mixed Bacteria Limosilactobacillus fermentum and Staphylococcus carnosus in the Meat Curing Process with a Reduced Amount of Sodium Nitrite

Abstract: The aim of the research was to estimate the possibility of using mixed bacteria cultures consisting of Lactobacillus fermentum S8 and Staphylococcus carnosus ATCC 51365 in the meat curing process with a reduced amount of sodium nitrite and to study the effect of bacteria on residual nitrites and nitrates, nitrosyl pigments content, colour, pH, redox potential, microbiologic, and the sensory quality of a cooked meat product. The study was performed on heat treated three-model meat treatments in cans: (C) a cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…The most popular microbial hurdles in the studies included in this review were combined starter cultures applied to meat [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. The use of a mixture of non-starter protective cultures to inhibit spoilage bacteria or/and foodborne pathogens was also assessed [ 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…The most popular microbial hurdles in the studies included in this review were combined starter cultures applied to meat [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. The use of a mixture of non-starter protective cultures to inhibit spoilage bacteria or/and foodborne pathogens was also assessed [ 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ].…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that the concentration of the salts did not exert a significantly different effect on the growth of the LAB evaluated; however, a relationship was found between the concentration and the strain evaluated, although it should be noted that the lowest growth was 4.5 log (CFU/mL). Therefore, nitrite and nitrate salts did not exert microbiological control; their use is more likely related to the organoleptic qualities that they contribute to the products [10,18,37].…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that the natural flora and starter cultures do not present a uniform distribution but are immobilized in the cavities of the sausage mixture, which act as growth nests, multiplying over time [60]; likewise, emulsion offers protection to the inoculums when they are located in the center and thus allows them to survive the thermal process. Bacteria are also known to temporarily inactivate under unfavorable conditions (latency) [37,52,60,63], which may have occurred in the third measurement performed on day 18 in treatments T3 and T1. Meanwhile, the differences over time (between the first three measurements and the last two) in the mesophilic organism and LAB counts were similar to those found in Laszkiewicz et al, 2021 [52], in which microbiological growth is associated with the deterioration of the packaging and the contamination of the product after cooking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meat products without or with reduced added nitrite/nitrate are characterized by high consumer acceptance [ 8 , 9 , 10 , 11 ]. Thus, the food industry has tried to replace synthesized nitrite with the use of vegetable extracts [ 10 , 12 , 13 , 14 ] and/or natural antimicrobials or the direct addition of bioprotective lactic acid bacteria cultures [ 6 , 15 , 16 , 17 ] and the strict control of the manufacturing process [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%